Technological Approaches To Organizing Independent Learning Based On The CreditModule System In Higher Education Institutions - Mirzayev Diyorbek Azamjonovich (Euro Asian Journal Publishing, 2025)
The credit-module system is an innovative framework aimed at increasing the efficiency of the educational process by promoting students' independent learning and self-management skills. Unlike traditional education, where students primarily acquire ready-made knowledge, this system encourages them to search, analyze, and draw conclusions independently. A key component of this system is electronic learning resources, which enhance the quality of education by fostering organizational skills, engagement, and practical competencies. These resources include electronic registers, assignments, graded tests, and virtual laboratories, accessible through online and offline platforms. The integration of modern information-communication technologies significantly improves the effectiveness of independent learning, allowing students to tailor their educational experiences. The main objectives of electronic learning resources in higher education involve structuring independent learning, setting clear goals, monitoring progress, and aligning with national training programs. Additionally, these resources facilitate the modernization of curricula, the differentiation of student learning approaches, and the enhancement of the overall educational process. The credit-module system offers multiple forms of assessment, such as exams, tests, and project work, allowing students to accumulate credits and manage their learning flexibly. By incorporating innovative pedagogical methods and digital tools, this system enhances students' self-management skills, optimizes their time allocation, and ultimately improves the quality and effectiveness of higher education.
Keywords: independent learning; credit-module; modern technologies